2011
DOI: 10.1182/blood-2011-01-331835
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health-related outcomes in survivors of childhood cancer treated with HSCT versus conventional therapy: a report from the Bone Marrow Transplant Survivor Study (BMTSS) and Childhood Cancer Survivor Study (CCSS)

Abstract: HSCT is being increasingly offered as a curative option for children with hematologic malignancies. Although survival has improved, the long-term morbidity ascribed to the HSCT procedure is not known. We compared the risk of chronic health conditions and adverse health among children with cancer treated with HSCT with survivors treated conventionally, as well as with sibling controls. HSCT survivors were drawn from BMTSS (N ‫؍‬ 145), whereas conventionally treated survivors (N ‫؍‬ 7207) and siblings (N ‫؍‬ 402… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
156
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 46 publications
5
156
1
2
Order By: Relevance
“…We conclude that both the less frequent use of BU or TBI in the conditioning regimens as well as the lack of exposure to other cytotoxic agents prior to HSCT explain these more favorable outcomes. Similar to previous studies, the presence of cGVHD was a risk factor for non-hormonal chronic health conditions 14 and can be regarded especially harmful for SAA patients who otherwise have better long-term health prospects. For decades, TBI has been the most frequently applied myeloablative and immunoablative procedure for patients with leukemia undergoing HSCT.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We conclude that both the less frequent use of BU or TBI in the conditioning regimens as well as the lack of exposure to other cytotoxic agents prior to HSCT explain these more favorable outcomes. Similar to previous studies, the presence of cGVHD was a risk factor for non-hormonal chronic health conditions 14 and can be regarded especially harmful for SAA patients who otherwise have better long-term health prospects. For decades, TBI has been the most frequently applied myeloablative and immunoablative procedure for patients with leukemia undergoing HSCT.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with findings from other studies, AEs tended to increase in severity with expanding follow-up time. 6,14 Of the survivors with the longest follow-up of ⩾ 20 years, 50% had at least one severe or disabling (grade 3-4) late effect. SAA patients had notably lower burdens of late effects, consistent with the report from Sanders et al 15 SAA patients had not received other cytotoxic therapies prior to HSCT, and majority of them had been conditioned with CY.…”
Section: Discussionmentioning
confidence: 99%
“…This determining role of preparative regimens is in accordance with previous studies that identified TBI as a risk factor for more frequent and more severe late effects in pediatric HSCT recipients. 2,16,17 This was not observed in a BMTSS study describing self-reported complications in mostly adult patients. 18 Child-specific adverse events like growth retardation might account for this difference.…”
Section: Discussionmentioning
confidence: 75%
“…1 It is now well known that these patients require attentive and continued follow-up into adulthood, due to late and very late complications such as endocrinopathies, growth and development disturbances, and second malignancies. The particularly high prevalence of late effects among HSCT recipients 2 should be a major concern of pediatric hematologists. This increased morbidity has often been attributed to the late toxicity of preparative regimens.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, there is a paucity of data regarding pediatric and adolescent and young adult survivors of childhood BMT and their transition to adulthood. It is critical that attention is given to this subset of BMT survivors, for they bring with them a unique set of potential complications.…”
Section: Introductionmentioning
confidence: 99%